The Influence of Transformational Leadership on Employee Career Development Case Study on PT. Pegadaian Branch of Pematangsiantar City - Butar-Butar , Diana Florenta; Karo-Karo, Perlaban; Ginting, Margono; Mayanta, Hendri (ProBisnis : Jurnal Manajemen, 2024)
This study aims to determine the influence of transformational leadership in employee career development at PT. Pegadaian, Pematangsiantar City Branch, the type of research used is quantitative. The population in this study were all employees at PT. Pegadaian, Pematangsiantar City branch and the number of samples in this study was 30 respondents (covering the entire population of the data source in this study using a research instrument in the form of a questionnaire and the processed data was tested using SPSS Version 25. The validity test for transformational leadership can be seen from having the lowest r count value of 0.376 while the r table is 0.349, so 0.376> 0.34 and it can be stated that all are valid. Meanwhile, the validity test for career development can be seen from all statements having the lowest r count value of 0.365 while the r table is 0.349, so 0.365> 0.349 and it can be stated that all statements are valid. Based on the calculation results, the Cronbach's Alpha value for transformational leadership is 0.842, which indicates that this questionnaire is reliable (consistent) because the Cronbach's Alpha value is> 0.7, while from the results of the reliability test, the value of Cronbach's Alpha for the career development variable is 0.839, which means it is greater than the threshold value of 0.7. This shows that all questionnaire instruments have good internal consistency, so they are reliable for use in research. For the t-test, the transformational leadership variable has a sig. value of 2.04841 and the tcount result> ttable, (10.9215> 2.04841), then Ha is accepted and Ho is rejected, so it can be concluded that the price coefficient partially has a significant effect on employee career development at PT Pegadaian Branch Kota Pematangsiantar.